PENGEMBANGAN MODUL BERBASIS PENEMUAN TERBIMBING UNTUK MATERI HIMPUNAN PADA PEMBELAJARAN MATEMATIKA SISWA KELAS VII SMPN I LEMBAH GUMANTI - -, Nurhayati - (Pendidikan Matematika, 2014)
This research was conducted due to the importance of learning materials in thelearning process. They could facilitate the students to learn independently.Unfortunately, the use of the Student Worksheet had not yet been able to help thestudents learn by themselves as the materials presented were very short anddifficult to be understood unless the teacher explained them. To overcome thisproblem, a guided finding-based learning module for teaching set topic wasdeveloped. This research was aimed at producing a guided finding-based learningmodule which was valid and practical. This was a developmental research whichused ADDIE model. This model consisted of five phases including Analysis,Design, Develop, Implement and Evaluate. The result of the validity andpracticality test showed that the guided finding-based learning module developedhad been very valid and practical.